Composite flame retardant, waterproof layer and environment-friendly flame-retardant macromolecular self-adhesive waterproof coiled material
By using composite flame retardant and modified waterproof layer in the waterproof roll, combined with composite ultra-refined metal hydroxide of magnesium hydroxide and aluminum hydroxide, the existing waterproof rolls have poor waterproof performance, flammable and toxic. The problems caused by gas have achieved high flame retardancy, strength and corrosion resistance.
Patent Information
- Application Number
- CN202411610028.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-12
- Publication Date
- 2025-02-18
AI Technical Summary
The existing waterproof coils have problems such as poor waterproof performance, flammable, and halogenated gases, resulting in safety hazards and fire accidents.
Using a composite flame retardant and a waterproof layer, a composite ultra-refined metal hydroxide is formed by modifying starch and polymer flame retardant combined with magnesium hydroxide and aluminum hydroxide to prepare a high flame retardant and high strength environmentally friendly resistor. Burn polymer self-adhesive waterproof coil.
It achieves waterproofing effects of high flame retardancy, high strength, impact resistance, acid and alkali chemical media corrosion resistance, and low temperature resistance, avoiding the problems of flammable and halogen flame retardants producing toxic gases.
Smart Images

Figure CN119463309A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of waterproof coiled materials, and more specifically, relates to a composite flame retardant and waterproof layer and an environmentally friendly flame retardant polymer self-adhesive waterproof coiled material. Background Art
[0002] In recent years, with the acceleration of my country's urbanization, the rapid development of urban infrastructure, the unprecedented prosperity of the construction industry, the continuous expansion of market demand, and the rise of high-rise buildings have brought opportunities and hope for local investment attraction and economic development. Building waterproofing is a necessary link in construction projects. Waterproofing work is directly related to the fundamental safety of buildings. The quality of waterproofing projects will directly affect the safety and survival of buildings. In the field of construction, common building waterproofing solutions are mainly based on traditional sealing methods such as cement waterproofing, asphalt coating, and rigid sealing. The principle is simple, the materials are random, and the engineering technology content is low. Therefore, the waterproof performance is poor, which easily leads to safety problems such as leakage. In particular, due to the chaotic structure of traditional waterproof materials, the waterproof sheets produced are usually thicker, with small specific surface area, poor impact resistance, low tensile strength, and easy to tear. Problems such as tearing greatly hinder the waterproof material from playing a role and seriously damage the waterproof performance of its own material. Moreover, in addition to the problem of poor waterproof effect (once the waterproof layer is damaged, water will flow, flammability and poor thermal stability will occur), traditional waterproof materials also have problems such as difficult construction and high labor intensity. In underground waterproofing projects, waterproof membranes are prone to safety problems such as water flow and leakage due to damage from hard objects and ground subsidence.
[0003] In addition, existing waterproofing membranes are easy to burn and have poor heat resistance. When burning, they release heat at a high rate, have a high calorific value, and spread the flame quickly, making them difficult to extinguish. Although existing waterproofing membranes are mostly flame-retardant with halogen flame retardants, their combustion easily produces halogenated gases (fluorine, chlorine, bromine, and iodine). In addition to their own strong toxicity affecting the human respiratory system, the resulting reduction in visibility also makes it impossible for people to identify escape routes. Moreover, when this gas encounters water vapor, it will generate hydrogen halides, which will corrode some equipment and buildings, and easily cause serious fire accidents.
[0004] Therefore, it is urgent to propose a new flame retardant polymer waterproof membrane to solve the problems of waterproofing, flammability, and generation of halogenated gases existing in traditional waterproof membranes. Summary of the invention
[0005] The purpose of the present invention is to provide a composite flame retardant and waterproof layer and an environmentally friendly flame retardant polymer self-adhesive waterproof roll material in view of the deficiencies of the prior art. The present invention provides an environmentally friendly flame retardant polymer self-adhesive waterproof roll material with high flame retardancy, high strength, impact resistance, acid and alkali chemical medium corrosion resistance, and low temperature resistance.
[0006] In order to achieve the above-mentioned object, the first aspect of the present invention provides a composite flame retardant, which is prepared by mixing, stirring and granulating an intumescent flame retardant and a composite ultrafine metal hydroxide;
[0007] The intumescent flame retardant is prepared by mixing and stirring modified starch and a polymer flame retardant;
[0008] The components of the composite ultrafine metal hydroxide include magnesium hydroxide and aluminum hydroxide.
[0009] According to the present invention, preferably, the modifying agent for preparing the modified starch is maleic anhydride (MAH) and / or 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO).
[0010] According to the present invention, preferably, the method for preparing the modified starch comprises: mixing starch (St) with maleic anhydride and performing esterification treatment to obtain esterified starch; mixing the esterified starch with 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, and performing drying treatment to obtain the modified starch.
[0011] According to the present invention, preferably, the temperature of the esterification treatment is 60-75° C., the time is 2.5-3.5 hours, and the esterification system is stirred every 3-10 minutes.
[0012] According to the present invention, preferably, based on the total weight of the composite flame retardant, the content of the starch is 25-35%, the content of the maleic anhydride is 5-25%, the content of the 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide is 1-15%, the content of the polymer flame retardant is 1-15%, and the content of the composite ultrafine metal hydroxide is 45-55%.
[0013] According to the present invention, preferably, the polymer flame retardant is ammonium polyphosphate (APP).
[0014] According to the present invention, preferably, the method for preparing the composite ultrafine metal hydroxide comprises: mixing the magnesium hydroxide and aluminum hydroxide and grinding them by ball milling to obtain the composite ultrafine metal hydroxide.
[0015] According to the present invention, preferably, the usage ratio of the magnesium hydroxide to the aluminum hydroxide is (0.8-1.2): (0.8-1.2).
[0016] According to the present invention, preferably, the particle size of the composite ultrafine metal hydroxide is 90-130 mesh.
[0017] The second aspect of the present invention provides a waterproof layer, which is prepared by sequentially blending and plasticizing, and then crosslinking and modifying by ultraviolet light irradiation with high-density polyethylene (HDPE), low-density polyethylene (LLDPE), ethylene-octene copolymer (POE), ethylene-butyl acrylate-glycidyl methacrylate copolymer (PTW), a composite flame retardant, titanium dioxide particles, a photoinitiator, a crosslinking agent, and an antioxidant;
[0018] The composite flame retardant is the composite flame retardant mentioned above.
[0019] According to the present invention, preferably, the photoinitiator is at least one of benzophenone (BP), 4-chlorobenzophenone and methyl o-benzoylbenzoate.
[0020] According to the present invention, preferably, the crosslinking agent is at least one of triallyl isocyanurate (TAIC), dicumyl peroxide and vinyl triethoxysilane.
[0021] According to the present invention, preferably, the raw materials of the waterproof layer are composed of the following components in parts by weight: 50-60 parts of high-density polyethylene, 10-15 parts of low-density polyethylene, 10-15 parts of ethylene-octene copolymer, 10-15 parts of ethylene-butyl acrylate-glycidyl methacrylate copolymer, 10-30 parts of composite flame retardant, 2-3 parts of titanium dioxide particles, 4-6 parts of photoinitiator, 4-6 parts of cross-linking agent and 0.5-1 part of antioxidant.
[0022] According to the present invention, preferably, the voltage of the ultraviolet light irradiation is 8-12 kV.
[0023] The third aspect of the present invention provides an environmentally friendly flame-retardant polymer self-adhesive waterproof roll material, the waterproof roll material comprising a buffer layer, an upper surface self-adhesive layer, a waterproof layer, a lower surface self-adhesive layer and an isolation layer arranged in sequence from top to bottom;
[0024] The waterproof layer is the above-mentioned waterproof layer;
[0025] The upper surface self-adhesive layer is a plurality of strip-shaped adhesive layers spaced apart on the waterproof layer;
[0026] The lower surface self-adhesive layer is fully adhered to the waterproof layer.
[0027] According to the present invention, preferably, the materials of the upper surface self-adhesive layer and the lower surface self-adhesive layer are independently waterproof hot melt adhesives.
[0028] According to the present invention, preferably, the material of the buffer layer is polyester filament singed geotextile.
[0029] According to the present invention, preferably, the material of the isolation layer is a double silicon isolation film.
[0030] In the present invention, the preparation of the environmentally friendly flame-retardant polymer self-adhesive waterproof membrane includes the following steps:
[0031] (1) Preparation of composite flame retardants, such as Figure 1 Shown
[0032] S1: mixing the magnesium hydroxide and the aluminum hydroxide and grinding them by ball milling to obtain the composite ultrafine metal hydroxide;
[0033] S2: Esterification, starch and MAH raw materials are mixed and put into a mixer to mix evenly, and heated for esterification (68°C, stirred once every 5 minutes) for 3 hours to obtain esterified starch; DOPO is added to the esterified starch, DOPO-MSt is obtained after mixing and sent to a feeder, and then sent to a hot air dryer for drying to obtain the modified starch;
[0034] S3: stirring and mixing the modified starch and ammonium polyphosphate evenly, adding the composite ultrafine metal hydroxide of S1 and mixing;
[0035] S4: Granulate the mixed and stirred materials in step S3 to prepare a composite flame retardant.
[0036] (2) Preparation of waterproof layer
[0037] S5: high-density polyethylene, low-density polyethylene, ethylene-octene copolymer, ethylene-butyl acrylate-glycidyl methacrylate copolymer, the above-mentioned composite flame retardant, titanium dioxide particles, photoinitiator, crosslinking agent and antioxidant, each raw material is mixed and put into a mixer, then sent to a feeder, and then sent to a hot air dryer for drying. The dried material is transported to a feed buffer bin through the feeder;
[0038] S6: plasticizing and extruding, the material dried in step S5 is plasticized by heating the screw section of a single screw extruder in sections, the screw section is divided into 10 sections, the temperature of each section from section 1 to section 10 is 50°C, 180°C, 190°C, 190°C, 190°C, 190°C, 190°C, 195°C, 195°C, 195°C, and the screw speed is 200rpm;
[0039] S7: extrusion molding, extruding the raw material mixture plasticized in step S6 into a mold through the extrusion section of the single-screw extruder, with the temperature of the extrusion section set to 200° C., to obtain a waterproof sheet layer;
[0040] S8: Cooling and forming, the waterproof sheet layer obtained in step S5 is pulled to the forming roller, the forming roller has a 3-roll calender and a 6-circulation cooling roller, the temperature of the lower roller is set to 35°C, the temperature of the middle roller is set to 60°C, the temperature of the upper roller is set to 45°C, and the temperature of the cooling roller is set to 35°C;
[0041] S9: UV irradiation cross-linking modification, the waterproof sheet layer formed by cooling in step S8 is passed through a UV irradiation box to be UV irradiated cross-linking modification to obtain a waterproof layer.
[0042] (3) Preparation of waterproof membrane
[0043] S10: first coating, coating the upper surface of the waterproof layer pulled in step S9 with self-adhesive adhesive and covering with a buffer layer geotextile by strip bonding method;
[0044] S11: second coating, the lower surface of the waterproof layer pulled by step 10 is coated with glue, and the glue coating in this step is full coating, and the isolation layer is a double silicon isolation film;
[0045] S12: trimming and rolling up, the coiled material from step S11 is adjusted in width according to the required specifications, the trimming machine is started to trim the edges, and then the meter is set to measure the length and roll up to obtain the environmentally friendly flame-retardant polymer self-adhesive waterproof coiled material.
[0046] The beneficial effects of the technical solution of the present invention are as follows:
[0047] 1. The present invention provides an environmentally friendly flame-retardant polymer self-adhesive waterproof membrane with high flame retardancy, high strength, impact resistance, acid and alkali chemical medium corrosion resistance, and low temperature resistance.
[0048] 2. The composite flame retardant of the present invention can be highly flame retardant, smoke suppressant, and environmentally friendly. The present invention uses the composite flame retardant to replace the halogen flame retardant to suppress the generation of smoke during the combustion process.
[0049] 3. The modified starch of the present invention and the use of the modified starch as a carbon source for an intumescent flame retardant can solve the problem of easy separation of the multifunctional components of the intumescent flame retardant and easy agglomeration of the flame retardant particles, which is beneficial to improving the flame retardant efficiency.
[0050] 4. Since the intumescent flame retardant of the present invention has deficiencies in heat resistance, moisture stability and smoke suppression, the present invention chooses to compound metal oxides with the intumescent flame retardant. Metal oxides have the advantages of environmental protection, low toxicity, low cost and stable performance, which can solve the shortcomings of the intumescent flame retardant.
[0051] 5. The metal oxides selected in the present invention are magnesium hydroxide (Mg(OH)2) and aluminum hydroxide (Al(OH)3). Magnesium hydroxide has good carbonization during combustion, but its fluidity is not as good as that of aluminum hydroxide. The present invention compounds magnesium hydroxide and aluminum hydroxide, and then grinds them to obtain a composite ultrafine metal hydroxide. This composite ultrafine metal hydroxide has good flame retardant and smoke suppression effects, and improves the flame retardant efficiency of the composite flame retardant.
[0052] 6. The present invention adds polyolefin elastomers (ethylene-octene copolymer (POE), ethylene-butyl acrylate-glycidyl methacrylate copolymer (PTW)) to the waterproof layer system to improve the flexibility of the waterproof layer.
[0053] 7. The present invention adopts ultraviolet light irradiation cross-linking technology to greatly improve the overall stability and high temperature resistance of the waterproof layer. Specifically, the present invention adds an appropriate amount of a reinforced cross-linking photoinitiator system, i.e., a photoinitiator and a multifunctional cross-linking agent, to the polyolefin, and irradiates it with ultraviolet light under certain conditions. The photoinitiator absorbs specific ultraviolet light to induce the production of active macromolecular free radicals. After a rapid cross-linking reaction between the macromolecular free radicals and the cross-linking agent, the long-chain macromolecules of the polyolefin are chemically linked into a polyolefin supramolecular structure with a three-dimensional network structure, thereby enhancing the overall stability and high temperature resistance of the waterproof layer material.
[0054] 8. The present invention uses the peeling zone theory, and the waterproofing membrane is covered with an environmentally friendly hot-melt pressure-sensitive adhesive self-adhesive layer on both sides, and then covered with an isolation layer and a buffer layer respectively to obtain a composite structure flame-retardant polymer self-adhesive waterproofing membrane target product. Among them, the upper surface self-adhesive layer is respectively strip-type compositely bonded to the waterproof layer and the buffer layer, so that the waterproof layer and the concrete form a physical mortise and tenon structure, thereby improving its waterproof effect; the lower surface self-adhesive layer is fully covered with glue, which improves the overall product bonding performance. The waterproof layer of the waterproofing membrane of the present invention is a formulated composite waterproof layer. The composite structure of the waterproof layer can overcome the problems of the existing materials without buffer, peeling zone and weak bonding. The peeling zone between the waterproof layer and the bonded base surface (referring to the concrete base surface) can prevent the base surface deformation from affecting the waterproof layer, causing it to be broken and damaged.
[0055] Other features and advantages of the present invention will be described in detail in the following detailed description. BRIEF DESCRIPTION OF THE DRAWINGS
[0056] The above and other objects, features and advantages of the present invention will become more apparent through a more detailed description of exemplary embodiments of the present invention with reference to the accompanying drawings.
[0057] Figure 1 A schematic diagram of the preparation process of a composite flame retardant provided in Example 1 of the present invention is shown. DETAILED DESCRIPTION
[0058] The preferred embodiments of the present invention will be described in more detail below. Although the preferred embodiments of the present invention are described below, it should be understood that the present invention can be implemented in various forms and should not be limited by the embodiments set forth herein. On the contrary, these embodiments are provided to make the present invention more thorough and complete, and to fully convey the scope of the present invention to those skilled in the art.
[0059] In the following embodiments and comparative examples:
[0060] Starch (St): industrial grade starch, Changchun Dacheng Corn Co., Ltd.
[0061] Maleic anhydride (MAH): analytical grade, Tianjin Komiou Chemical Reagent Co., Ltd.
[0062] DOPO: DOPO, Shouguang Weidong Chemical Co., Ltd.
[0063] Ammonium polyphosphate: Zhengzhou Guanda Chemical Products Co., Ltd.
[0064] HDPE: Brand: DGDB2480, Shandong Qilu Petrochemical Company.
[0065] LLDPE: Brand number is DFDA-7042, Maoming Petrochemical Company.
[0066] POE: Brand number 8832, Dow Chemical Company, USA.
[0067] PTW: Brand name is GMA, DuPont Company, USA.
[0068] Titanium dioxide granules: Model: titanium dioxide granules-7000RGF pure white-Ningbo Masterbatch-PE-color number 10007, Ningbo Masterbatch Co., Ltd.
[0069] Antioxidant: Brand No. 1010, Linyi Sanfeng Chemical Co., Ltd.
[0070] Example 1
[0071] This embodiment provides a composite flame retardant. The preparation of the composite flame retardant includes:
[0072] S1: mixing the magnesium hydroxide and the aluminum hydroxide and grinding them by ball milling to obtain the composite ultrafine metal hydroxide; the particle size of the composite ultrafine metal hydroxide is 90-130 mesh;
[0073] S2: Esterification, starch and MAH raw materials are mixed and put into a mixer to mix evenly, and heated for esterification (68°C, stirred once every 5 minutes) for 3 hours to obtain esterified starch; DOPO is added to the esterified starch, DOPO-MSt is obtained after mixing and sent to a feeder, and then sent to a hot air dryer for drying to obtain the modified starch;
[0074] S3: stirring and mixing the modified starch and ammonium polyphosphate (APP) uniformly, adding the composite ultrafine metal hydroxide of S1 and mixing;
[0075] S4: Granulate the mixed and stirred materials in step S3 to prepare a composite flame retardant.
[0076] As shown in Table 1, based on the total weight of the composite flame retardant, the content of the starch is 30%, the content of the maleic anhydride (MAH) is 10%, the content of the 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO) is 5%, the content of the ammonium polyphosphate (APP) is 5%, the content of the magnesium hydroxide is 25%, and the content of the magnesium hydroxide is 25%.
[0077] This embodiment also provides a waterproof layer, and the preparation of the waterproof layer includes:
[0078] S5: 50 parts of high-density polyethylene (HDPE), 10 parts of low-density polyethylene (LLDPE), 12 parts of ethylene-octene copolymer (POE), 11 parts of ethylene-butyl acrylate-glycidyl methacrylate copolymer (PTW), 20 parts of the above-mentioned composite flame retardant, 2 parts of titanium dioxide particles, 5 parts of photoinitiator, 5 parts of cross-linking agent and 1 part of antioxidant are mixed and put into a mixer, then sent to a feeder, and then sent to a hot air dryer for drying. The dried material is transported to the feed buffer bin through the feeder;
[0079] S6: plasticizing and extruding, the material dried in step S5 is plasticized by heating the screw section of a single screw extruder in sections, the screw section is divided into 10 sections, the temperature of each section from section 1 to section 10 is 50°C, 180°C, 190°C, 190°C, 190°C, 190°C, 190°C, 195°C, 195°C, 195°C, and the screw speed is 200rpm;
[0080] S7: extrusion molding, extruding the raw material mixture plasticized in step S6 into a mold through the extrusion section of the single-screw extruder, with the temperature of the extrusion section set to 200° C., to obtain a waterproof sheet layer;
[0081] S8: Cooling and forming, the waterproof sheet layer obtained in step S5 is pulled to the forming roller, the forming roller has a 3-roll calender and a 6-circulation cooling roller, the temperature of the lower roller is set to 35°C, the temperature of the middle roller is set to 60°C, the temperature of the upper roller is set to 45°C, and the temperature of the cooling roller is set to 35°C;
[0082] S9: UV irradiation cross-linking modification, the waterproof sheet layer cooled and formed in step S8 is passed through a UV irradiation box for UV irradiation cross-linking modification, the voltage of the UV irradiation is 10kV, and a waterproof layer is obtained.
[0083] This embodiment also provides an environmentally friendly flame-retardant polymer self-adhesive waterproof coiled material, the preparation of which includes:
[0084] S10: First coating, the upper surface of the waterproof layer pulled in step S9 is coated with self-adhesive glue by strip bonding method (to form a physical mortise and tenon structure between the waterproof layer and the concrete later), and covered with a buffer layer of polyester filament singed civil engineering cloth;
[0085] S11: second coating, the lower surface of the waterproof layer pulled by step 10 is coated with glue, and the glue coating in this step is full coating, and the isolation layer is a double silicon isolation film;
[0086] S12: trimming and rolling up, the coiled material from step S11 is adjusted in width according to the required specifications, the trimming machine is started to trim the edges, and then the meter is set to measure the length and roll up to obtain the environmentally friendly flame-retardant polymer self-adhesive waterproof coiled material.
[0087] Table 1
[0088]
[0089]
[0090] The waterproof membranes prepared in the above examples and comparative examples were tested under the same test conditions, and the test results are shown in Table 2 below.
[0091] Table 2
[0092]
[0093]
[0094] From Table 1 and Table 2, we can see that:
[0095] The test results of the halogen content of smoke after the waterproof membranes of various embodiments and comparative examples were as follows: no toxic halogenated gas was found.
[0096] Comparison between Example 1 and Comparative Example 3: Al(OH)3 was not added to the composite flame retardant formula of Comparative Example 3, and agglomeration and uneven dispersion occurred during the manufacturing process of the composite flame retardant of Comparative Example 3. When the composite flame retardant of Comparative Example 3 was added to the production of the waterproof layer of the roll material, an obvious infusible point appeared on the outer surface of the waterproof layer, resulting in a significant decrease in its mechanical properties.
[0097] Comparison between Example 1 and Example 2 and Comparative Example 2: After adding the composite flame retardant to the waterproof layer system, adding a certain proportion of POE and PTW can effectively alleviate the attenuation of the mechanical properties of the overall system.
[0098] Comparison between Example 1 and Example 3: The use of ultraviolet light irradiation cross-linking modification can improve the overall thermal aging retention rate of the coil.
[0099] Comparison between Example 1 and Comparative Example 4: Adding composite ultrafine metal hydroxide to prepare a composite flame retardant is beneficial to improving the heat resistance of the system, and a large amount of thick smoke is generated during the combustion test of Comparative Example 4.
[0100] Comparison between Example 1 and Comparative Example 4: Adding a large amount of flame retardant material will lead to a significant attenuation of the physical and mechanical properties of the waterproof layer system.
[0101] Comparison between Example 1 and Comparative Example 1: The present invention uses a mortise and tenon structure in production. Compared with a single-layer structure, the waterproof performance of the bonding between the roll material of the present invention and the post-cast concrete is significantly improved, and no breakage is found during the test.
[0102] Comparison between Example 1 and Comparative Example 2: Adding the composite flame retardant to the waterproof layer system greatly improves the flame retardant effect of the system, but will cause a certain degree of attenuation of the physical and mechanical properties.
[0103] The embodiments of the present invention have been described above, and the above description is exemplary, not exhaustive, and is not limited to the disclosed embodiments. Many modifications and changes will be apparent to those skilled in the art without departing from the scope and spirit of the described embodiments.
Claims
1. A composite flame retardant, characterized in that: The composite flame retardant is prepared by mixing, stirring and granulating an intumescent flame retardant and a composite ultrafine metal hydroxide; The intumescent flame retardant is prepared by mixing and stirring modified starch and a polymer flame retardant; The components of the composite ultrafine metal hydroxide include magnesium hydroxide and aluminum hydroxide.
2. The composite flame retardant according to claim 1, wherein The modifying agent for preparing the modified starch is maleic anhydride and / or 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide; The method for preparing the modified starch comprises: mixing starch with maleic anhydride and performing esterification treatment to obtain esterified starch; mixing the esterified starch with 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide and performing drying treatment to obtain the modified starch; Preferably, the temperature of the esterification treatment is 60-75° C., the time is 2.5-3.5 hours, and the esterification system is stirred every 3-10 minutes.
3. The composite flame retardant according to claim 2, wherein: Based on the total weight of the composite flame retardant, the content of the starch is 25-35%, the content of the maleic anhydride is 5-25%, the content of the 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide is 1-15%, the content of the polymer flame retardant is 1-15%, and the content of the composite ultrafine metal hydroxide is 45-55%.
4. The composite flame retardant according to claim 1, wherein The polymer flame retardant is ammonium polyphosphate.
5. The composite flame retardant according to claim 1, wherein The preparation method of the composite ultrafine metal hydroxide comprises: mixing the magnesium hydroxide and aluminum hydroxide and grinding them by ball milling to obtain the composite ultrafine metal hydroxide; The dosage ratio of the magnesium hydroxide to the aluminum hydroxide is (0.8-1.2): (0.8-1.2); The particle size of the composite ultrafine metal hydroxide is 90-130 meshes.
6. A waterproof layer, characterized in that: The waterproof layer is prepared by sequentially blending and plasticizing high-density polyethylene, low-density polyethylene, ethylene-octene copolymer, ethylene-butyl acrylate-glycidyl methacrylate copolymer, composite flame retardant, titanium dioxide particles, photoinitiator, crosslinking agent and antioxidant, and then crosslinking and modifying them by ultraviolet light irradiation. The composite flame retardant is the composite flame retardant according to any one of claims 1 to 5.
7. The waterproof layer according to claim 6, wherein: The photoinitiator is at least one of benzophenone, 4-chlorobenzophenone and methyl o-benzoylbenzoate; The crosslinking agent is at least one of triallyl isocyanurate, dicumyl peroxide and vinyl triethoxysilane; The raw materials of the waterproof layer are composed of the following components in parts by weight: 50-60 parts of high-density polyethylene, 10-15 parts of low-density polyethylene, 10-15 parts of ethylene-octene copolymer, 10-15 parts of ethylene-butyl acrylate-glycidyl methacrylate copolymer, 10-30 parts of composite flame retardant, 2-3 parts of titanium dioxide particles, 4-6 parts of photoinitiator, 4-6 parts of cross-linking agent and 0.5-1 part of antioxidant.
8. The waterproof layer according to claim 6, wherein: The voltage of the ultraviolet light irradiation is 8-12 kV.
9. An environmentally friendly flame-retardant polymer self-adhesive waterproof membrane, characterized in that: The waterproof coiled material comprises a buffer layer, an upper surface self-adhesive layer, a waterproof layer, a lower surface self-adhesive layer and an isolation layer arranged in sequence from top to bottom; The waterproof layer is the waterproof layer according to any one of claims 6 to 8; The upper surface self-adhesive layer is a plurality of strip-shaped adhesive layers spaced apart on the waterproof layer; The lower surface self-adhesive layer is fully adhered to the waterproof layer.
10. The environmentally friendly flame-retardant polymer self-adhesive waterproof membrane according to claim 9, wherein: The materials of the upper surface self-adhesive layer and the lower surface self-adhesive layer are independently hot-melt pressure-sensitive adhesive for waterproofing; The material of the buffer layer is polyester filament singed geotextile; The material of the isolation layer is a double silicon isolation film.